ON THE SPECTRUMS OF SOME CLASS OF SELFADJOINT SINGULAR DIFFERENTIAL OPERATORS - (:unkn) unknown (ANKARA UNIV, FAC SCI, 2016)
In this work, based on the Everitt-Zettl and Calkin-Gorbachuk methods in terms of boundary values all selfadjoint extensions of the minimal operator generated by some linear singular multipoint symmetric differential operator expression for first order in the direct sum of Hilbert spaces of vector functions on the right semi-axis are described. Later structure of the spectrum of these extensions is investigated.
Keywords: Everitt-Zettl and Calkin-Gorbachuk methods; singular multipoint; differential operators; selfadjoint extension; spectrum; EXTENSIONS